Pengaruh Budaya Organisasi Motivasi terhadap Kepuasan Kerja dan Kinerja Karyawan Industri Rokok di Jawa Timur - Usman, Umedi (Universitas Brawijaya, Indonesia, 2009)
This research was based on a phenomenon that the bad quality of Indonesia's human resources and an issue that unsatisfied workers cause disharmony between workers and employers. Managing a company of any activity scale is not separated from individual and group behavior. Fulfilling one's will and needs will be implemented by people through their daily behaviors. The behavior that someone performs in fulfilling hid needs, his action sometimes deviates from the regulations both written and verbal, therefore; an instrument is needed to control it. The existence of motivation of stimulus is important for people to do any activities in their work environments. Organizational culture and motivation are different but their existence will have significant effects on employees' job satisfaction and performance. Therefore; it is not a superfluous thing that every leader, employee and company owner must give his attention on employees' organizational culture, work motivation, job satisfaction, and performance in achieving company's goals so that everybody who is involved in the company will enjoy prosperity together. The purpose of this research is to measure and to obtain deductive and empirical authentication about the effects of organizational culture on motivation and employee's job satisfaction along with his performance in the cigarette industry in east java. The type of method which is used is explanatory research which is one conducted through explaining the relationship of one variable with other variables from the examined object.